Outcome Based Education: Analisis Kemampuan Mahasiswa dalam Mengembangkan Project Berbasis Critical Thinking. - Raras Kartika Sari (Supermat : Jurnal Pendidikan Matematika, 2026)
The study aims to analyze the application of the Outcome-Based Education (OBE) approach in learning Advanced differential equations with laplace transform material to analyze the critical thinking skills of Mathematics Education students. The study was conducted using a descriptive qualitative method, with a case study approach involving two subjects of Mathematics Education students who took the Advanced Differential Equations course. The subjects were taken by purposive sampling. The research instruments used included observation sheets, interview sheets and video results of course projects. Data analysis was carried out through analysis of field observation notes and analysis of student video project results. The research stage was carried out with the stages of data collection, data reduction in the form of video project results, data presentation and drawing conclusions. The results showed that students had fulfilled various elements of critical thinking. In subject 1 in making the project, it had not fulfilled the clarity element while in subject 2 it had fulfilled all elements of critical thinking such as focus, reasons, Interface, situation, clarity, and overview through developing a video project using the OBE application strategy